Biodiversity of Ciliated Protozoa in Soil Ecosystems and Assessment of their Potential as Bio-indicatiors of soil quality - Hai Thi Thuy Luu (Bournemouth University, 2020)
The aim of this study is to investigate the abundance and species richness of ciliated protozoa in naturaland agricultural soils, and to determine the relationship between physio-chemical soil properties and the occurrence of the species and abundance of ciliates in order to determine the usefulness of soil ciliates as bio-indicatorsof soil quality. In order to do so, investigating biodiversity of soil ciliates and analysing physical and chemical characteristics of soils in the study sites was conducted. Controlled experimental conditions were used to assess theimpact of specific contamination factors i.e., the metal copper, herbicide glyphosate and insecticide cypermethrin. In addition, the taxonomy of soil ciliate species found at study sites was investigated to identify rare and new species and to enhance the knowledge of ciliate biodiversity in soils.